An alarm pheromone increases the responsivity of amygdaline-hippocampal neurons. - Molina-Jiménez, Tania; Gutiérrez-García, Ana G.; Contreras, Carlos M. (Salud Mental)
The capability to perceive and emit alarm substances, such as 2-hep-tanone, makes animals aware of the presence of danger, leading to some strategies directed towards survival. Strategies of survival involve emotional memory which is processed by deep temporal lobe structures, such as amygdaloid complex and hippocampus. In the Wi-star rat, 2-heptanone produces anxiety-like behavior and an increased firing rate of basal amygdaline neurons. However, it is unknown whether 2-heptanone modifies the responsivity of medial amygdaline-hippocampal connection. Therefore, we placed a group (n=10) of Wistar rats in a plexiglass cage impregnated with 2-heptanone. Rats from control group (n=10) were introduced into a similar clean cage. Twenty four hours later we obtained single-unit extracellular recordings from the hippocampus (CA1-CA3) neurons identified by their connection to medial amygdala. Although the basal neuronal firing rate was similar between groups, first order interval distribution histogram analysis showed that 2-heptanone produced shorter intervals of firing rate. Peristimulus histograms indicated that: i) the amygdaline stimulation produces an increased firing rate in hippocampal neurons; and ii) this response is increased and enlarged on the 2-heptanone group. Since a single exposure to an alarm pheromone seems to facilitate the amygdala-hippocampal connection, results suggest the initial formation of contextual memories related with fear.